NASIONALISASI PERUSAHAAN MULTINASIONAL AMERIKA SERIKAT DI VENEZUELA PADA MASA PEMERINTAHAN HUGO CHAVEZ - Ismaya Saputri (HI 16 UMY 010, 2016)
*10 Hugo Chavez is the president of Venezuela who rejected the United State and neoliberalism. To inhibit neoliberalism in Venezuela, Chavez implement the policy of nationalization. Chavez’s nationalization policy toward the US multinational corporation will be discussed in this paper. And will be analyzed using game theory and Johan Galtung’s asymmetric relation. Some of the issues will be discussed in this paper is the background of Hugo Chavez, the reasons of nationalization policy, US interest in Venezuela and the way of Hugo Chavez convince the United Stated to accept a new scheme which offered by Chavez. Nationalization is Hugo Chavez’s way to save the economy of Venezuela which has long suffered deterioration caused by neoliberalism. The way of Hugo Chavez convince the United Stated to accept nationalization policy is giving compensation and shows the serious attitude of Chavez, accompanied by making law about the nationalization policy.